The standardization and certification procedures of cryogenic equipment in Kazakhstan: 10th International Conference on Cryocrystals and Quantum Crystals (Final part) - Shinbayeva, A.; Drobyshev, A.; Drobyshev, N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The complex of procedures on stepwise carrying out actions of standardization and certification of liquid nitrogen, argon and oxygen gasificator G-200 is considered. In the process of organization of standardization and certification procedures the set of regulatory documents was developed that allow starting small-scale production of gasificators in Kazakhstan. Thus the emphasis on the potential incorporation of the requirements of such documents is placed from the Eurasian Economic Union.